Studi Karakteristik Propertis Tanah di Kecamatan Polen Kabupaten TTS - Tri M Sir; Dolly W. Karels; Wilhelmus Bunganaen; I Made Udiana (JURNAL FORUM TEKNIK SIPIL (J-ForTekS), 2023)
Knowing soil characteristics is very important for an engineer to ensure the safety of buildings above the ground. Therefore, conducting a soil investigation in the laboratory and field testing The island of Timor, especially in the Polen sub-district, Timor Tengah Selatan district, has fine-grained soil deposits. In the sub-district area, a large dam is being built, namely the Temef Dam and the main road link connecting one city and four regencies on the island of Timor also. This study aims to determine the characteristics of the soil both physically and mechanically through laboratory testing. The results showed that the location in Puna Village was clay of low plasticity, while the Loli Village had high plasticity clay deposits. The higher of soil's plasticity index, the higher the potential for swelling of the soil. The increased swelling potential causes the low shear strength of the soil. Clay with low shear strength cannot support the construction load on it. Therefore, before the construction of the building on it, it is necessary to improve the soil. In addition to its weaknesses, on the other hand, impermeable clay is used in the dam core material, where the location of material extraction is still within reach so that the work becomes economical.